Efficacité du média French Listening & Speaking pour améliorer la production orale des étudiants de la section française de l’UNIMED - Rahma Dewi Shinta (Didacticofrancia Journal Didactique du FLE, 2026)
This study aims to analyze the effectiveness of the French Listening & Speaking application in improving the oral production skills of students in the French Education Program at Unimed. The main problem identified is the students’ low proficiency in pronunciation, vocabulary, fluency, and grammar, especially in the themes Sortie and Voyage et Vacances. The research employs a quantitative method using a quasi-experimental design with a one-group pretest-posttest model. The sample consists of 19 third-semester students from Class B, selected through purposive sampling. Data were collected using an oral production test administered before and after the treatment. The pre-test results show an average score of 68.05, indicating that students’ initial ability remained low. After using the media, the post-test average increased to 84, showing a notable improvement. The N-Gain analysis also confirms that the improvement is significant. Based on these findings, the French Listening & Speaking media is proven effective in enhancing students’ oral production skills. The application supports the development of pronunciation, vocabulary, fluency, and confidence in speaking French. Therefore, integrating this digital media into foreign language teaching can serve as an innovative and effective pedagogical alternative.